Endothelial function and gene expression in perivascular adipose tissue from internal mammary arteries of obese patients with coronary artery disease. (November 2017) - Cybularz, Maria; Langbein, Heike; Zatschler, Birgit; Brunssen, Coy; Deussen, Andreas; Matschke, Klaus; Morawietz, Henning
Abstract: Background and aims: Obesity is a risk factor for endothelial dysfunction and atherosclerosis. However, perivascular adipose tissue can release adipokines and other unknown adipose-derived relaxing factors. Therefore, we investigated the impact of obesity on vascular function and expression of genes in perivascular adipose tissue from internal mammary arteries of patients with coronary artery disease undergoing coronary artery bypass grafting. Methods: The vessel function was compared between groups of patients with a body-mass index (BMI) between 25 and 30 kg/m 2 . The groups did not differ in age, gender (males), and ejection fraction. Vascular segments of internal mammary arteries were examined in a Mulvany myograph. Following preconstriction with noradrenaline, dose–response curves were assessed for relaxation with acetylcholine and sodium nitroprusside. Results: Maximum contraction in response to potassium and noradrenaline was increased in obese patients with a BMI >30 kg/m 2 . EC50 of endothelium-dependent relaxation was impaired in patients with a BMI above 25, but below 30 kg/m 2 . Sodium nitroprusside-mediated maximal relaxation was not different between study groups. Integrin alpha X chain (ITGAX/CD11c) and macrophage mannose receptor (MRC1/CD206) expression was reduced in perivascular adipose tissue of patients with a BMI above 30 kg/m 2, while adiponectin (ADPQ) expression was increased in the same tissue. Conclusion: Our data suggest a partially reduced endothelial function in internal mammary arteries of adipose patients with a BMI between 25 and 30 kg/m 2 undergoing coronary artery bypass grafting surgery. Increased adiponectin expression in perivascular tissue might contribute to maintenance of endothelial function in obese patients with a BMI above 30 kg/m 2 .